Complete genome sequence of Acidaminococcus fermentans type strain (VR4T). Issue 1 (July 2010) - Chang, Yun-Juan; Pukall, Rüdiger; Saunders, Elizabeth; Lapidus, Alla; Copeland, Alex; Nolan, Matt; Glavina Del Rio, Tijana; Lucas, Susan; Chen, Feng; Tice, Hope; Cheng, Jan-Fang; Han, Cliff; et al.
Abstract Acidaminococcus fermentans (Rogosa 1969) is the type species of the genusAcidaminococcus, and is of phylogenetic interest because of its isolated placement in a genomically little characterized region of theFirmicutes .A. fermentans is known for its habitation of the gastrointestinal tract and its ability to oxidizetrans -aconitate. Its anaerobic fermentation of glutamate has been intensively studied and will now be complemented by the genomic basis. The strain described in this report is a nonsporulating, nonmotile, Gram-negative coccus, originally isolated from a pig alimentary tract. Here we describe the features of this organism, together with the complete genome sequence, and annotation. This is the first complete genome sequence of a member of the familyAcidaminococcaceae, and the 2, 329, 769 bp long genome with its 2, 101 protein-coding and 81 RNA genes is part of theG enomic E ncyclopedia of B acteria and A rchaea project.